STAKEHOLDERS' MAPPING AND STRATEGY FOR RESTORING PEATLAND FOREST IN WEST TANJUNG JABUNG JAMBI, INDONESIA - Ignatius Adi Nugroho; Darwo Darwo; Dhany Yuniarti (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2021)
Peatland forests became the centre of discussions in Indonesia because 33% of 2.4 million hectares burned in 2014. This research aims to describe the stakeholders' position and their logic in choosing a strategy for peatland forest areas. The result shows that nine stakeholders were actively involved in peatland forest restoration in West Tanjung Jabung Regency. Based on categorization, the analysis points out that all stakeholders had occupied key players' position. Further analysis using a ladder of participation criteria found two models of participation, i.e. citizen power and tokenism. However, the value of citizen power is higher than tokenism that is 56% and 44%, respectively. It means that stakeholders should develop partnership and other models in citizen power criteria to reach their targets. It also means that trust is an essential variable in the relationship among stakeholders and should be developed in peatland forest restoration. The consequence of this research is that stakeholders can improve two strategies, i.e. collaborative forest management and community-based forest management.